A review of heating/cooling processes using nanomaterials suspended in refrigerants and lubricants. (June 2020) - Yang, Liu; Jiang, Weixue; Ji, Weikai; Mahian, Omid; Bazri, Shahab; Sadri, Rad; Badruddin, Irfan Anjum; Wongwises, Somchai
Highlights: The effects of nanomaterial addition to the refrigerants/lubricants. Nanorefrigerants and nanolubricants in the refrigeration and HVAC systems. On the basis of heat transfer enhancement and thermophysical properties behavior. Considering various influential applicable parameters of nanomaterials. Abstract: Over the last century, nanomaterial-based cooling/heating working fluids have been considered one of the most potent alternatives to the conventional heat transfer medium. Likewise, as one prevalent series of the applications and by utilization of much more potent eco-friendly fluids, the constant everyday attempt in the area of refrigeration, HVAC, and other associated systems has involved the usage of nanorefrigerants/nanolubricants. Indeed, the addition of high thermal conductive nanoparticles to the low thermal conductive traditional base fluids is one of the most attention-grabbing areas of research. In this current scientific review article, by considering boiling, condensation, or the related phenomena, the heat transfer rate and the thermophysical properties have been targeted to investigate the substantial effect of nanoparticle addition to common refrigerants or lubricants. At the end, the relevant research gaps, namely the heat transfer rate at an atomic level, the inconsistent behavior of nanofluids, the phase change enthalpy level, and other possible fields, were detected as a helpful benchmark for future studies.